2021
DOI: 10.3390/molecules26165087
|View full text |Cite
|
Sign up to set email alerts
|

Redox Conversions of 5-Methyl-6-nitro-7-oxo-4,7-dihydro-1,2,4triazolo[1,5-a]pyrimidinide L-Arginine Monohydrate as a Promising Antiviral Drug

Abstract: This article presents the results of a study of electrochemical transformations in aqueous and aprotic media of 5-methyl-6-nitro-7-oxo-4,7-dihydro-1,2,4-triazolo[1,5-a]pyrimidinide l-arginine monohydrate (1a, Triazid) obtained by electrochemical methods and ESR spectroscopy. The effect of pH on the current and the reduction potential of 1a in an aqueous Britton–Robinson buffer solution was studied. It was found that 1a is irreversibly reduced in aqueous acidic media on a glassy carbon electrode in one stage wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Since the formation of electroactive groups occurs during the functionalization of carbon black. It is possible that the single wave 6e process of TD reduction [12] is divided into 2 waves, corresponding, presumably, to the accession of 2 and 4 e [18,45,48,63]. This shape of the cathodic signal is unacceptable for analytical purposes.…”
Section: Electroanalytical Performance Of the Spce's Towards Tdmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the formation of electroactive groups occurs during the functionalization of carbon black. It is possible that the single wave 6e process of TD reduction [12] is divided into 2 waves, corresponding, presumably, to the accession of 2 and 4 e [18,45,48,63]. This shape of the cathodic signal is unacceptable for analytical purposes.…”
Section: Electroanalytical Performance Of the Spce's Towards Tdmentioning
confidence: 99%
“…Previously, we have found that TD is irreversibly reduced to one six‐electron wave with the formation 5‐methyl‐6‐amino‐7‐oxo‐4,7‐dihydro‐1,2,4‐triazolo[1,5‐ a ]pyrimidinide l‐arginine. The reduction of the nitro group is accompanied by intermediates of a radical nature, which may be the reason for the appearance of biological activity in the substance [12]. Currently, multicenter clinical trials for influenza viruses are being carried out in clinics of the Russian Federation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we studied the redox transformations of substances of a number of triazolotriazines (Triazavirin® and Triazide) [18,19]. The studies demonstrated that the electrochemical behavior of a structural analog may differ due to the difference in the structure and requires an individual approach to the investigation of its redox mechanism.…”
Section: Introductionmentioning
confidence: 99%